2014
DOI: 10.1007/s11164-014-1872-6
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic properties of TiO2-functionalized tiles: influence of ceramic substrate

Abstract: To confer self-cleaning properties to ceramic tiles through photocatalytic phenomena, TiO 2 is deposited as thin films on their surface. However, photocatalytic properties could be strongly influenced by physico-chemical characteristics of the ceramic support. For this reason, this investigation was aimed to study the influence of porosimetric characteristics of different ceramic tiles on adsorption and photocatalytic activity induced by deposited TiO 2 film in the presence of UV light. Experimental data in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Various approaches to continuous photoreactor design have been proposed, including optical fiber, double-skin sheet, fluidized bed, and annular reactors. [173][174][175][176] The transparent part should be designed to allow for homogeneous irradiation of the catalyst bed and its material should have minimal absorption in the solar spectrum to minimize energy losses. Reflection losses from the surface of the reactor should be minimized, for example, by applying anti-reflective coatings or surface treatments.…”
Section: Flow Chemistry and Continuous Photoreactorsmentioning
confidence: 99%
“…Various approaches to continuous photoreactor design have been proposed, including optical fiber, double-skin sheet, fluidized bed, and annular reactors. [173][174][175][176] The transparent part should be designed to allow for homogeneous irradiation of the catalyst bed and its material should have minimal absorption in the solar spectrum to minimize energy losses. Reflection losses from the surface of the reactor should be minimized, for example, by applying anti-reflective coatings or surface treatments.…”
Section: Flow Chemistry and Continuous Photoreactorsmentioning
confidence: 99%
“…Meseguer et al (15) demonstrated the photocatalytic capacity of ceramic glazes as a new functionality of ceramic tiles with applications in construction (such as flooring and wall covering) and in the field (such as air purification and water cleaning). Photocatalytic ceramic tiles are typically prepared by coating the ceramic tile with anatase TiO 2 using various deposition techniques, such as spray deposition (16)(17)(18)(19), screen printing (20,21) and sol-gel methods (22)(23)(24). However, several critical aspects must be considered to obtain suitable TiO 2 -containing ceramic materials: firing temperature and adhesion of the TiO 2 film/particles to the substrate (21,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ducman et al [2] studied the formation of photocatalytic coatings on ceramics building products (tiles, glass and roofing tiles) by spraying of a TiO 2 isopropanol suspension. Another scientific work related to TiO 2 functional tiles was performed by Vaiano et al [24] who examined the influence of the substrates porosity on the photocatalytic activity of coated ceramic tiles. However, no work was found, up to now, in the literature regarding the application of Chemical Vapour Deposition (CVD) for the production of coated heavy clay ceramics.…”
Section: Introductionmentioning
confidence: 99%